College Freshman English - Fernando, Jovita N. (Mandaluyong City, Philippines : National Book Store, 1988)
In Series II, grammatical structures are introduced in a completely functional, stimulating, and we believe, effective approach to grammar usage and composition writing. The natural-sounding practice sentences greatly simplify the task of both teacher and student. Often they appear in the form of meaningful paragraphs on Philippine customs and practices, historical events or some illuminating selection, so that the student adds to his knowledge and broadens his cultural outlook as he studies his grammar.
Unit I. Word order: a review -- Unit II. The word -- Unit III. Diction - usage and vocabulary -- Unit IV. The sentence -- Unit V. The paragraph -- Unit VI. The whole composition -- Unit VII. Letter writing.
Includes bibliographical references.
Keywords: ENGLISH LANGUAGE -- STUDY AND TEACHING